Assembly of inorganic [Mo2S2O2]2+ panels connected by selenite anions to nanoscale chalcogenide–polyoxometalate clusters. Issue 6 (2nd March 2016) - Zang, Hong-Ying; Chen, Jia-Jia; Long, De-Liang; Cronin, Leroy; Miras, Haralampos N.
Abstract : Supramolecular assembly of [Mo2 S2 O2 ] 2+ /SeO3 2− based building blocks, mediated by controlling the hetero-atom ratio, leads to the formation of clusters {(Mo2 O2 S2 ) x (OH) y (SeO3 ) z (H2 O) w } n − exhibiting ring, "exo" and "endo" architectures with multiple binding sites and cation recognition functionality. Abstract : We describe how supramolecular assembly, mediated by control of the ratio of the hetero-atoms in the units [Mo2 S2 O2 ] 2+ and SeO3 2− leads to the formation of new types of building blocks, [(Mo2 O2 S2 )3 (OH)4 (H2 O)6 (SeO3 )] = Mo6 and [(Mo2 O2 S2 )2 (OH)2 (H2 O)4 (SeO3 )] = Mo4 which are linked in an type of inorganic 'panelling' to the assembly of a range of new clusters1–3 with the general formula {(Mo2 O2 S2 ) x (OH) y (SeO3 ) z (H2 O) w } n −, where x, y, z, w, n = [8, 0, 20, 8, 24] for1, [14, 14, 17, 8, 20] for2 and [8, 8, 8, 0, 8] for3 . Cluster1, a rare example of inorganic cryptand, exhibits an elliptical "endo" motif defining an anisotropic ellipse with the dimensions 1.7 × 1.0 nm, with pores ranging from 5.3 to 6.4 Å and site selective cation recognition properties; cluster2 exhibits an "exo" structural motif constructed by 3 × Mo6 and 2 × Mo4 panels spanning a cross shape 2.4 × 2.0 nm and cluster3 a ring shaped structure of a 1.5 nm in diameter. The control of endo vs. exo topology as a function of the Se : Mo ratio is reflected to the difference in surface area of ca. 500 Å 2 between clusters1 and2 intermolecular interactions and proton conduction properties, and this work shows that very simple synthetic parameters can critically change the structure and properties of all-inorganic nanoscale chalcogenide–polyoxometalates.